2009
DOI: 10.1073/pnas.0905890106
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis spreads by surfing on waves of surfactant

Abstract: The bacterium Bacillus subtilis produces the molecule surfactin, which is known to enhance the spreading of multicellular colonies on nutrient substrates by lowering the surface tension of the surrounding fluid, and to aid in the formation of aerial structures. Here we present experiments and a mathematical model that demonstrate how the differential accumulation rates induced by the geometry of the bacterial film give rise to surfactant waves. The spreading flux increases with increasing biofilm viscosity. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
123
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 35 publications
7
123
0
Order By: Relevance
“…It has been shown that differences in surfactin concentration along the biofilm can produce surface tension gradients that are sufficient to pull B. subtilis pellicles upward on glass slides. However, although the gradients in surface tension may be large enough to pull the biofilm, the total reduction in surface tension due to surfactin production during pellicle growth is only about 10% (25). Although the spatiotemporal location, transport, and absorption of surfactin molecules have not been characterized, this suggests that the concentration of surfactin at the biofilm surface may be fairly small.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been shown that differences in surfactin concentration along the biofilm can produce surface tension gradients that are sufficient to pull B. subtilis pellicles upward on glass slides. However, although the gradients in surface tension may be large enough to pull the biofilm, the total reduction in surface tension due to surfactin production during pellicle growth is only about 10% (25). Although the spatiotemporal location, transport, and absorption of surfactin molecules have not been characterized, this suggests that the concentration of surfactin at the biofilm surface may be fairly small.…”
Section: Discussionmentioning
confidence: 83%
“…The ability of B. subtilis biofilms to resist wetting may be considered particularly surprising in light of the fact that B. subtilis secretes surfactin (25,26), a biomolecule that enhances biofilm spreading by lowering the effective surface tension of liquids and that could similarly be expected to increase wetting. It has been shown that differences in surfactin concentration along the biofilm can produce surface tension gradients that are sufficient to pull B. subtilis pellicles upward on glass slides.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of quorum-sensing controlled surfactant molecules in several biofilm-forming bacteria (9)(10)(11)(12) indicates that the mechanism that we describe here in S. aureus represents a widespread mechanism of biofilm structuring. It is possible that enzymes that degrade biofilm polymers provide additional structuring for which there is some recent evidence in S. aureus (7,8); however, how such enzymes contribute to biofilm maturation awaits in-depth investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacteria synthesize biosurfactants (1). Marangoni flows driven by surface-tension gradients can account for the flagellar-independent colony expansion of some species, such as Bacillus subtilis that produces surfactin (12)(13)(14). However, this cannot be the general mechanism driving swarm-fluid spreading because most swarming is flagella dependent and does not always require production of surfactants (1).…”
mentioning
confidence: 99%